Active disturbance rejection control for active suspension system - Faried bin Hasbullah (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
A vehicle suspension system is the main component in a ground vehicle that functions to achieve good ride comfort by isolating vibration of the road from the passenger. Active suspension system has the capability to continuously adjust itself, hence has a better design trade-offs compared to a conventional suspension system. Active disturbance rejection control (ADRC) is a relatively new control method and has not been thoroughly investigated in the area of ride comfort and advanced automotive suspension. In this thesis, ADRC with and without input decoupling transformation (IDT) is proposed to improve the ride quality performance of a vehicle with active suspension system according to several performance criteria: minimizing vehicle body accelerations, suspension working space, and road holding. Three vehicle models: quarter-car, half-car, and full-car model were used in this thesis. The models used in the analysis were limited to discrete models which break down the vehicle model into lumped systems. Through experimental simulation studies, the ability of the proposed controllers to cope with varying process is investigated. The optimized controllers are then compared to an ideal skyhook control to benchmark the performance. Results show that ADRC-IDT was able to produce comparable performance to a typical ADRC control structure, but with less number of control parameters. Both controllers were able to significantly reduce vehicle body acceleration while maintaining other responses. Furthermore, On the whole, it is shown that the performance of the optimized ADRC and ADRC-IDT is close to the performance of an ideal skyhook control especially for the sprung mass vertical acceleration which is the main indicator of vehicle ride comfort.